Pengaruh Indeks Pembangunan Manusia (Ipm),Tenaga Kerja, Dan Pendidikan Terhadap Pertumbuhan Ekonomi Di Provinsi Jawa Tengah - Rusmarinda, Rakhmawati; , Dr. Didit Purnomo, M,Si (2016)
This research entitled "The Influence of the Human Development Index (HDI), Labor, and education against The Economic Growth in The Province of Central Java". Economic growth is one of the indicators of succes in development. Economic growth in Central Java by 2013 are still at the fifth position when compared with other provinces in the region of Java - Bali. This research aims to analyze the influence of the human development index (HDI), labor, and education in Central Java province. Type of data used in this research is secondary data obtained from various books, journals and the Central Bureau of statistics. Methods of analysis used was the OLS (Ordinary Least Square). Based on this study it can be concluded that the positive effect of the HDI variables and not significantly to economic growth, while the influential labor variable is positive and significant and the influential education variable is negative and significant. Keyword : Economic Growth, The Human Development Index (HDI), Labor, and Education